Dispersive solid phase extraction combined with dispersive liquid–liquid extraction for the determination of BTEX in soil samples: ant colony optimization–artificial neural network. (17th March 2015) - Khajeh, Mostafa; Moosavi‐Movahedi, Ali Akbar; Shakeri, Mohammad; Musavi Zadeh, Fatemeh; Khajeh, Ahmad; Bohlooli, Mousa
<x xml:space="preserve">Abstract</x> In this study, dispersive solid phase extraction combined with dispersive liquid–liquid extraction has been developed for the extraction of benzene, toluene, ethylbenzene, and xylenes isomers (BTEX) in soil samples prior to gas chromatography–mass spectrometry. The BTEX were extracted from soil sample into acetonitrile by dispersive solid phase extraction method, and the extract was then used as dispersive solvent in dispersive liquid–liquid extraction procedure. Ant colony optimization–artificial neural network (ACO–ANN) has been employed to develop the model for simulation and optimization of this method. The volume of dispersive solvent, volume of extraction solvent, extraction time, and ultrasonic time were the input variables, while the multiple response function (Rm) of analytes was the output. The optimum operating condition was then determined by ant colony optimization method. At the optimum conditions, the limit of detections of 0.12–0.75 ng g−1 was obtained for the BTEX. The developed procedure was then applied to the extraction and determination of BTEX in the soil samples and one certified soil. Copyright © 2015 John Wiley & Sons, Ltd.